The Effect of Compensation, Work Environment, and Organizational Commitment on Performance with Job Satisfaction as An Intervening Variable - Dyan Mayla; M. Arief (Kusuma Negara Business School, 2020)
High company employee performance can be achieved if all the elements that exist within the agency are well integrated, and able to play its role in accordance with the needs and desires of the public and employees. Therefore we need support of compensation, work environment, organizational commitment, and job satisfaction to improve the performance of these employees. The purpose of this study is to analyze and determine the effect of work environment compensation and organizational commitment to employee performance through job satisfaction.This study aimed to examine the effect of compensation, work environment, and organizational commitment to improve the performance of these employees either partially or simultaneously in Pt. Gobel Dharma Sarana Karya. The method used is descriptive and verification method with a sample of 53 respondents. Data were collected by using questionnaires and data analysis used is path analysis.The results showed that compensation, work environment, and organizational commitment partially influence job satisfaction and performance. Whereas job satisfaction does not mediate the effect of compensation, work environment, and organizational commitment on performance